Post traumatic stress disorder and coping strategies among adult survivors of earthquake, Nepal - Ishwari Adhikari Baral; Bhagawati K.C (BMC Psychiatry, 2019)
Abstract Background Post traumatic stress disorder (PTSD) is the most frequently reported psychiatric morbidity among the survivors of natural disasters. It is the main hindrance to rehabilitate their life. However its prevalence particularly in Nepal is largely unknown. Aims and objectives To investigate the prevalence of post traumatic stress disorder and use of coping strategies among the adult survivors of earthquake. Methods A cross- sectional descriptive study was carried out on a sample of 291 adult survivors after 10 months of Nepal Earthquake 2015. Study setting was Nuwakot district with multistage sampling (cluster sampling and systematic random sampling) method. PTSD checklist-5 was used to measure PTSD, and adapted and modified brief cope scale was used to assess coping strategies. Data were analyzed using descriptive and inferential statistics (independent t-test and one-way ANOVA) at 5% level of significance. Results Study findings revealed that PTSD was prevalent among 24.10% of adult survivors with highest intrusion symptoms (3.24 ± 0.71). It was significantly associated with age (p = 0.017), sex (p = 0.013), education (p < 0.0001) and injury to self (p = 0.003). Elderly, females, illiterates and those who were injured during earthquake are at more risk for PTSD. Highest used coping strategy was active coping (2.92 ± 0.51). Survivors not having PTSD scored more on active coping (p < 0.0001) and self distraction coping (p = 0.006) while those with PTSD mostly used passive coping (p < 0.0001), religious coping (p < 0.0001) and substance use coping (p < 0.0001). Conclusion Earthquake poses significant impact on mental health of the survivors. After 10 months of devastating earthquake, prevalence of PTSD among the survivors is high. Maladaptive coping strategies further increase possibility of PTSD. Effective screening and awareness program regarding promotion of positive coping strategies among the vulnerable groups should be reinforced for prevention of psychiatric morbidity among the survivors of earthquake.